2019
DOI: 10.1534/genetics.119.302493
|View full text |Cite
|
Sign up to set email alerts
|

Drift and Directional Selection Are the Evolutionary Forces Driving Gene Expression Divergence in Eye and Brain Tissue ofHeliconiusButterflies

Abstract: Characterization of gene expression patterns across species - and the evolutionary forces driving them - can reveal processes that have remained conserved across species, as well as those that have changed in a species- specific manner...

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 102 publications
3
37
0
Order By: Relevance
“…Moreover targeted RT-PCR on a subset of these genes suggested that selection could occur simultaneously in the coding sequence and regulatory elements of these genes. Overall our work, together with previous studies (Catalan, Höhna, et al. 2019; Catalan, Macias-Munoz, et al.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Moreover targeted RT-PCR on a subset of these genes suggested that selection could occur simultaneously in the coding sequence and regulatory elements of these genes. Overall our work, together with previous studies (Catalan, Höhna, et al. 2019; Catalan, Macias-Munoz, et al.…”
Section: Discussionsupporting
confidence: 76%
“…2010). It is worth pointing out that while most of these studies on a specific group of visual genes have increased our understanding of color perception, only a few of them have addressed the adaptive evolutionary signature of an entire butterfly eye (Catalan, Höhna, et al. 2019; Catalan, Macias-Munoz, et al.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the main genes involved in D. melanogaster phototransduction were found as single copies in Lepidoptera and were upregulated in H. melpomene heads such as Gqα , β and γ , norpA , inaD , ninaC , Calx , trp , trpl , Arr1 , Arr2 , and stops (fig. 1; Table 2, for additional orthocluster analysis in butterflies see Catalán et al. 2018).…”
Section: Resultsmentioning
confidence: 99%
“…For both models roughly 99% of the prior MASV is greater than 0.01, while roughly 5% of the posterior MASV is greater than 0.01, further indicating that the models are producing effectively constant trajectories. Computing such a significance threshold to reject a constant rate model can be computed using Monte Carlo simulation [ 58 ]. The HSMRF and GMRF produce very similar average error and fold change, though the distributions of these metrics for the GMRF are more tightly focused around the target values (MAD of 0, FC of 1), and the GMRF has slightly tighter credible intervals.…”
Section: Resultsmentioning
confidence: 99%